NATURALISASI PEMAIN ASING DALAM HUKUM KONSTITUSI INDONESIA - Silitonga, Marudut Parulian; Kristina, Dina (Fakultas Hukum Universitas Kristen Indonesia, 2025)
A basic right of every human being is to choose the citizenship they want. In every country's constitution regulates how everyone can have citizenship in their country. In the world of sports, especially football, every country in the world wants to participate in the World Cup competition organized by FIFA. And also football players take part in the World Cup competition. The Republic of Indonesia wants its national team to participate in the World Cup competition, so PSSI as a national football organization recruits foreign players to become national players. For that, foreign players must become Indonesian citizens or what is called naturalization. Indonesia as a country of law, everyone must submit to the constitution in force in Indonesia, as stated in the 1945 Constitution of the Republic of Indonesia and the laws governing citizenship